Efectividad de varias combinaciones de nitrógeno, azufre, zinc, manganeso, boro y fitohormonas sobre el rendimiento y rentabilidad del Cacao Nacional. - Cedeño Loor, Diógenes Alejandro (2017)
The objective of this research was to verify the effectiveness of several combinations of nitrogen, sulfur, zinc, manganese, boron and phytohormones in the benefit and cost effectiveness of the National Cocoa, in a farm of Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López (ESPAM MFL), proving that fertilization is one of the fundamental parameters in cocoa crops benefit and that the use of hormonal bioregulators or phytohormones allow higher planting densities and accelerate cocoa production, which together increase the cost effectiveness obtained by the farmers of Manabi. In plant material used in the trial was a portion of EET-103, EET-575 and EET-476 National cocoa, five years old, with a density of 1,111 plants / ha; realize a DBCA with 10 treatments and 3 replicates, that is, 30 experimental units. Through the orthogonal design of Taguchi, and the computer-statistical tool Infostat, results were obtained on the performance in graphical form; later, through the agro economic evaluation, the profitability was determined. The results of the research, lower number of diseased fruits and vegetative brooms produced per plant, reflect the importance of balanced nutrition with macro and micronutrients in contrast to conventional fertilization with pre-established doses of NPK. In addition, the highest yield and economic benefit was obtained with the optimum combination: 450, 100, 5 and 5 kg / ha of nitrogen, sulfur, borax and Zn sulfate, respectively, plus the foliar application of the auxin-based phytogulator, gibberellins and cytokinins at doses of 0.5 L / ha.